The Role of Soy Phytoestrogens on Genetic and Epigenetic Mechanisms of Prostate Cancer - (:unkn) unknown (Academic Press, 2015)
Soy phytoestrogens are dietary components with considerable effects on reducing the incidence of prostate cancer. Epidemiological studies demonstrated that occurrence of prostate cancer is relatively low in Asia and Southern Europe, a status associated with consuming of soy isoflavones, such as genistein, daidzein, and glycitein. Soy phytoestrogens exert their activity on molecular mechanisms, including cell-cycle control, induction of apoptosis, inhibition of angiogenesis, and metastasis. In addition, they have antioxidant activity and show regulatory effect on the expression of genes involved in DNA damage and repair. Furthermore, the epigenetic regulation of gene expression can be modified by soy phytoestrogens. They show regulatory effects on gene activity by altering DNA methylation and/or histone modification patterns. In this chapter, we discuss the role of soy phytoestrogens on the genetic and epigenetic mechanisms of prostate cancer. We attempt to provide further insight in order to understand the underlying mechanisms of protective effects of soy phytoestrogens in preventing prostate cancer. © 2015 Elsevier Inc.
Keywords: Epigenetics; Genistein; Isoflavones; Prostate cancer; Soy phytoestrogens